Ultimate strength assessment of welded stiffened plates. (1st February 2015) - Tekgoz, M.; Garbatov, Y.; Guedes Soares, C.
Highlights: The effect of residual stress on the ultimate strength of a thin rectangular stiffened plate is studied. The analysis is performed by the finite element method. The heat source is defined as a moving heat one in order to simulate welding processes. Three types of welding sequences have been conducted for the stiffened panel. Modified material stress strain curves have been developed. Abstract: This work analyses the effect of residual stress on the ultimate strength of a thin rectangular stiffened and single plate. The analysis is performed by the finite element method employing commercial software. The heat source is defined as a moving heat one in order to simulate welding processes and consequently the corresponding residual stresses. Three types of welding sequences have been conducted for the stiffened panel. A sensitivity analysis is performed accounting for the plate thickness, heat source, speed and level of residual stresses. Modified material stress strain curves have been developed accounting for the plate thickness that can be directly used in the non-linear finite element analyses of ultimate strength of thin plates.